Powder curing agent as well as preparation method and use method thereof

By adding powder curing agent to the phenolic resin spray binder, including a specific proportion of silicon-containing compounds, the problems of slow hardening speed, low strength, high brittleness and surface sand loss in 3D printed sand are solved, and sand molds with faster hardening, higher strength and better toughness are achieved, and casting efficiency and quality are improved.

CN120243825APending Publication Date: 2025-07-04SHARED INTELLIGENT EQUIPMENT (ANHUI) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510389609.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

The existing phenolic resin spray adhesives have slow hardening speed, long box cleaning time, low sand strength, high brittleness, and surfaces are prone to moisture and sand loss, affecting the casting quality.

Method used

A powder curing agent is used, including silicon-containing compounds, metal oxides, metal hydroxides, amide polymers, glycol polymers and solid paraffin. By mixing and adding them to molded sand, spraying and printing with liquid organic ester curing agent and phenolic resin, it forms an efficient sand type.

Benefits of technology

It significantly improves the hardening speed and strength of the sand mold, shortens the box cleaning time, improves toughness and moisture resistance, avoids cracking and sand loss, and improves casting efficiency and quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a powder curing agent as well as a preparation method and a use method thereof, belongs to the field of curing agents, and aims to solve the problems of low sand mold hardening speed, long box cleaning time, low strength and the like caused by printing by adopting a phenolic resin jet binder. The powder curing agent comprises powder materials including a silicon-containing compound, a metal oxide, a metal hydroxide, an amide polymer, an ethylene glycol polymer and solid paraffin; wherein the weight ratio of the silicon-containing compound is 28%-70%, the weight ratio of the metal oxide is 8%-27%, the weight ratio of the metal hydroxide is 6%-18%, the weight ratio of the amide polymer is 5%-20%, the weight ratio of the ethylene glycol polymer is 4%-16%, and the weight ratio of the solid paraffin is 2%-12%. The strength of the sand mold is improved, the hardening speed of the sand mold is increased, the box cleaning time of the sand mold is shortened, and the situation that the surface of the sand mold is affected with damp and sand falls off is changed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of curing agents, and particularly relates to a powder curing agent. Background Art

[0002] 3D printing is a kind of rapid prototyping technology. By stacking materials layer by layer, three-dimensional objects can be printed. The materials that can be used for 3D printing include plastics, metals, ceramics, rubbers, glasses, sands, etc. 3D printing technology has developed rapidly and is widely used in various industries such as industrial design, architecture, engineering construction (AEC), automobiles, aerospace, medical, education, casting, etc.

[0003] In the casting industry, currently, the main types of binders used for sand bonding in the domestic and foreign casting 3D printing fields include furan resins for 3D printing, phenolic resins for 3D printing, inorganic binders for 3D printing, etc. Among them, furan resins for 3D printing have the characteristics of high sand strength, fast hardening speed, good sand regeneration performance, etc., and are currently widely used in the sand mold printing production of cast iron parts and non-ferrous metal parts; the sand molds printed with phenolic resins for 3D printing have the characteristics of not containing harmful elements such as nitrogen, phosphorus, and sulfur, being less affected by air humidity during the hardening process, being able to be heated for secondary hardening after drying to increase strength, having high high-temperature residual strength after casting, and small thermal expansion rate and thermal deformation rate, and are particularly suitable for the production of cast steel parts such as water pumps, valves, chemical equipment, and nuclear industry equipment, having advantages that cannot be replaced by 3D furan resins. However, in the actual research and application process of phenolic resins for 3D printing, there are still problems such as longer mold release time of sand molds than that of furan resins for 3D printing, lower room temperature strength than that of 3D furan resins, large brittleness of sand molds, and obvious sand dropping after long-term placement.

[0004] The authorized patent "A Silica Hydrogel Modified Cold-Setting Phenolic Resin" with the patent number CN115141329B provides a silica hydrogel cold-setting phenolic resin for 3D printing. This patent solves the problem of high brittleness of the resin at room temperature and has the characteristics of strong stability, good heat resistance, and high high-temperature strength after curing. However, for the resin described in this patent, water is generated during the phenolic reaction during preparation, water is introduced in the alkaline catalyst, and solvents are added during the preparation process. Eventually, the solvent content in the resin reaches 40% - 75%. The solvent in the resin not only does not participate in the chemical reaction during the reaction between the phenolic resin and the liquid organic ester curing agent but even affects the forward progress of the hardening reaction. During the process of 3D printing sand molds with cold-setting phenolic resin (hereinafter referred to as phenolic resin), the solvent in the resin volatilizes slowly. As the size and thickness of the printed sand mold increase, the solvent in the lower layer of the sand mold is difficult to volatilize, ultimately affecting the hardening speed, cleaning time, and room-temperature hardening strength of the sand mold. In addition, it has been verified that there are problems with high brittleness and poor toughness in the phenolic resin printed sand mold. Due to uneven stress during cleaning, lifting, and core assembly, the sand mold will crack or even break. In addition, when the printed sand mold is placed at room temperature for a long time, the surface of the sand mold is prone to moisture absorption and sand dropping problems, affecting the core strength, surface finish, and dimensional accuracy. Summary of the Invention

[0005] In view of the problems such as slow hardening speed, long cleaning time, and low sand mold strength of the sand mold products printed with phenolic resin as the printing jet binder and the sand mold mixed with liquid curing agent, it is necessary to propose a powder curing agent, its preparation method, and its usage method.

[0006] A powder curing agent, the powder materials included are silicon-containing compounds, metal oxides, metal hydroxides, amide polymers, ethylene glycol polymers, and solid paraffin; among them, the weight percentages of each component are respectively: silicon-containing compounds 28% - 70%, metal oxides 8% - 27%, metal hydroxides 6% - 18%, amide polymers 5% - 20%, ethylene glycol polymers 4% - 16%, and solid paraffin 2% - 12%.

[0007] Further, the silicon-containing compound can be one or more of silicides and silicates. Specifically, the silicide can be one or more of silicon dioxide, calcium silicide, magnesium silicide, silicon carbide, silicon nitride, and silicon chloride; the silicate can be one or more of sodium silicate, potassium silicate, magnesium silicate, aluminum silicate, calcium silicate, lithium silicate, and sodium metasilicate. Preferably, the silicide can be silicon dioxide, calcium silicide, and magnesium silicide; the silicate can be sodium silicate, potassium silicate, and calcium silicate.

[0008] Furthermore, the particle size of the silicon-containing compound powder is 50 mesh - 200 mesh. Preferably, the particle size of the silicon-containing compound powder is 70 mesh - 140 mesh.

[0009] Further, the metal oxide may be one or more of lithium oxide, sodium oxide, potassium oxide, magnesium oxide, calcium oxide, aluminum oxide, zinc oxide, iron oxide, barium oxide, titanium oxide; preferably, the metal oxide may be lithium oxide, sodium oxide, potassium oxide, calcium oxide.

[0010] Furthermore, the particle size of the metal oxide powder is 50 mesh - 200 mesh; preferably, the particle size of the metal oxide powder is 100 mesh - 200 mesh.

[0011] Further, the metal hydroxide may be one or more of calcium hydroxide, magnesium hydroxide, barium hydroxide, aluminum hydroxide, zinc hydroxide, iron hydroxide; preferably, the metal hydroxide may be calcium hydroxide, barium hydroxide, magnesium hydroxide, zinc hydroxide.

[0012] Furthermore, the particle size of the metal hydroxide powder is 50 mesh - 200 mesh; preferably, the particle size of the metal hydroxide powder is 50 mesh - 100 mesh.

[0013] Further, the amide polymer may be one or more of polyamide, polyimide, polyacrylamide, polycaprolactam, polyhexamethylene adipamide, polyamide ester, polycarbazole, heterocyclic polyamide; preferably, the amide polymer may be polyamide, polyimide, polyacrylamide.

[0014] Furthermore, the particle size of the amide polymer powder is 50 mesh - 200 mesh; preferably, the particle size of the amide polymer powder is 100 mesh - 200 mesh.

[0015] Further, the ethylene glycol polymer (abbreviation in English: PEG) may be one or more of PEG - 1500, PEG - 2000, PEG - 3000, PEG - 4000, PEG - 6000, PEG - 8000; preferably, the ethylene glycol polymer (abbreviation in English: PEG) may be PEG - 1500, PEG - 2000, PEG - 3000.

[0016] Furthermore, the particle size of the ethylene glycol polymer powder is 50 mesh - 200 mesh; preferably, the particle size of the ethylene glycol polymer powder is 60 mesh - 120 mesh.

[0017] Further, the solid paraffin may be microcrystalline wax and polyethylene wax.

[0018] Furthermore, the particle size of the solid paraffin powder is 50 mesh - 200 mesh; preferably, the particle size of the solid paraffin powder is 50 mesh - 100 mesh.

[0019] A preparation method of a powder curing agent, comprising:

[0020] S01, sequentially adding a silicon-containing compound powder in a weight ratio of 28%-70%, a metal oxide powder in a weight ratio of 8%-27%, and a metal hydroxide powder in a weight ratio of 6%-18% into a mixing device, and stirring the powders evenly;

[0021] S02, adding an amide polymer powder in a weight ratio of 5%-20% into S01, and stirring the powders evenly again;

[0022] S03, adding an ethylene glycol polymer powder in a weight ratio of 4%-16% and a solid paraffin powder in a weight ratio of 2%-12% into S02, and stirring the powders evenly again to obtain the powder curing agent.

[0023] A using method of a powder curing agent, comprising:

[0024] S11, adding a powder curing agent accounting for 0.3%-3% of the weight of the molding sand into the molding sand, and mixing evenly;

[0025] S12, adding a liquid organic ester curing agent accounting for 0.1%-0.6% of the weight of the molding sand into the product obtained in S11, and mixing evenly;

[0026] S13, adding the product obtained in S12 into the powder spreading device of a sand mold additive manufacturing device, and using the product obtained in S12 to spread a powder layer;

[0027] S14, spraying phenolic resin as a binder on the powder layer surface laid in S13, and circulating layer by layer to realize the printing of the sand mold.

[0028] Further, placing the sand mold obtained in S14 in a normal temperature environment and naturally hardening it for 2h-8h, the hardness of the sand mold can reach the requirements for cleaning the box. When using phenolic resin as a binder, printing a sand mold with molding sand mixed with the powder curing agent can shorten the cleaning box time by 3h-7h, greatly shortening the production beat of the molding process.

[0029] Advantages of the technical solution of the present invention:

[0030] The 28%-70% silicon-containing compound added in the powder curing agent can increase the strength of the sand mold by 10% to 25%.

[0031] The 8%-27% metal oxide added in the powder curing agent can accelerate the hardening speed of the sand mold by 10% to 30%, can shorten the cleaning box time of the sand mold by 1-3h, and can increase the strength of the sand mold by 5% to 15%.

[0032] Adding 6%-18% metal hydroxide to the powder hardener can increase the hardening speed of the sand mold by 15%-40%, shorten the cleaning time of the mold by 2-4 hours, and increase the strength of the sand mold by 10%-25%.

[0033] Adding 5%-20% amide polymer to the powder hardener can increase the room temperature strength of the sand mold by 10%-30% and the high temperature strength of the sand mold by 15%-30%.

[0034] Adding 4%-16% ethylene glycol polymer to the powder hardener can improve the toughness of the phenolic resin sand mold and avoid cracking or breaking of the sand mold during mold cleaning, lifting, and core assembly.

[0035] Adding 2%-12% solid paraffin to the powder hardener can improve the toughness and hardness of the phenolic resin sand mold, improve the moisture resistance of the phenolic resin sand mold, and improve the situation of sand dropping after the surface is affected by moisture. Description of the Drawings

[0036] None. Detailed Embodiments

[0037] To more clearly illustrate the technical solutions of the present invention, obviously, the following descriptions are some typical embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other solutions can also be obtained based on these embodiments.

[0038] The powder hardener described in the present invention is applicable to the additive manufacturing process and is used to cooperate with the application scenario of injection printing with room temperature-curing phenolic resin as the binder.

[0039] In one embodiment, the powder hardener described in the present invention includes powder components such as silicon-containing compounds, metal oxides, metal hydroxides, amide polymers, ethylene glycol polymers, and solid paraffin; among them, the weight ratios of each component are 28%-70% for silicon-containing compounds, 8%-27% for metal oxides, 6%-18% for metal hydroxides, 5%-20% for amide polymers, 4%-16% for ethylene glycol polymers, and 2%-12% for solid paraffin.

[0040] In another embodiment, the preparation method of the powder hardener includes

[0041] S01, adding silicon-containing compound powder with a weight ratio of 28%-70%, metal oxide powder with a weight ratio of 8%-27%, and metal hydroxide powder with a weight ratio of 6%-18% to the mixing equipment in sequence, and stirring the powder evenly;

[0042] S02, adding amide polymer powder with a weight ratio of 5%-20% to S01, and stirring the powder evenly again;

[0043] S03. Add ethylene glycol polymer powder with a weight ratio of 4% - 16% and solid paraffin powder with a weight ratio of 2% - 12% to S02, and stir the powders evenly again to obtain the powder curing agent.

[0044] Another implementation method of the powder curing agent includes:

[0045] S11. Add the powder curing agent accounting for 0.3% - 3% of the weight of the molding sand to the molding sand and mix evenly.

[0046] S12. Then add a liquid organic ester curing agent accounting for 0.1% - 0.6% of the weight of the molding sand to the product obtained in S11 and mix evenly.

[0047] S13. Add the product obtained in S12 to the powder feeder of the sand mold additive manufacturing equipment and use the product obtained in S12 to lay a powder layer.

[0048] S14. Use phenolic resin as a binder and spray it on the powder layer surface laid in S13, and cycle layer by layer to achieve the printing of the sand mold.

[0049] Examples of the preparation method of the powder curing agent described in the present invention are as follows.

[0050] Example 1

[0051] The preparation method of the powder curing agent described in the present invention includes:

[0052] 1) Sequentially add silica with a particle size of 100 mesh and a weight ratio of 28%, lithium oxide with a particle size of 200 mesh and a weight ratio of 15%, and calcium hydroxide powder with a particle size of 70 mesh and a weight ratio of 13% to the mixing equipment, and stir the three added powders evenly.

[0053] 2) Add polyamide powder with a particle size of 150 mesh and a weight ratio of 20% to the above mixture again, and stir again to make the two mix evenly.

[0054] 3) Add three kinds of powders, namely PEG - 1500 with a particle size of 80 mesh and a weight ratio of 12%, microcrystalline wax with a particle size of 70 mesh and a weight ratio of 7%, and polyethylene wax with a particle size of 50 mesh and a weight ratio of 5% to the above mixture again, and stir evenly again to obtain the powder curing agent described in the present invention.

[0055] Compared with the sand mold produced with the phenolic resin as the binder and the same kind of sand mold produced without mixing the powder curing agent of the present invention in the molding sand, the relevant performance of the sand mold produced with the powder curing agent prepared in Example 1 has been significantly improved, as shown in Table 1 specifically. Table 1 is a comparison table of various performance indexes of the sand mold produced or printed with the molding sand added with the powder curing agent prepared in Example 1 and the same kind of sand mold produced or printed with the molding sand without adding the powder curing agent.

[0056] Table 1 Comparison Table of Performance Indexes of Example 1

[0057]

[0058] It can be seen from the test results in Table 1 that after adding the powder curing agent of the present invention, various performance indexes of the sand mold have been significantly improved, achieving the expected effect.

[0059] Example 2

[0060] The preparation method of the powder curing agent of the present invention includes

[0061] 1) Add calcium silicide with a particle size of 70 mesh accounting for 36% by weight, barium oxide with a particle size of 150 mesh accounting for 18% by weight, zinc oxide with a particle size of 100 mesh accounting for 10% by weight, and magnesium hydroxide powder with a particle size of 100 mesh accounting for 10% by weight into the mixing equipment in sequence, and stir the four added powders evenly;

[0062] 2) Add polyacrylamide powder with a particle size of 100 mesh accounting for 13% by weight into the above mixture again, and stir again to make the two mix evenly;

[0063] 3) Add two kinds of powders, PEG - 3000 with a particle size of 120 mesh accounting for 4% by weight and polyethylene wax with a particle size of 90 mesh accounting for 9% by weight into the above mixture again, and stir evenly again to obtain the powder curing agent of the present invention.

[0064] Compared with the sand mold produced with the phenolic resin as the binder and the same kind of sand mold produced without mixing the powder curing agent of the present invention in the molding sand, the relevant performance of the sand mold produced with the powder curing agent prepared in Example 2 has been significantly improved, as shown in Table 2 specifically. Table 2 is a comparison table of various performance indexes of the sand mold produced or printed with the molding sand added with the powder curing agent prepared in Example 2 and the same kind of sand mold produced or printed with the molding sand without adding the powder curing agent.

[0065] Table 2 Comparison Table of Performance Indexes of Example 2

[0066]

[0067] As can be seen from the detection results in Table 2, after adding the powder curing agent of the present invention, the various performance indicators of the sand mold have been significantly improved, achieving the expected effect.

[0068] Example Three

[0069] The preparation method of the powder curing agent of the present invention includes

[0070] 1) Add magnesium silicide with a particle size of 140 mesh and a weight ratio of 48%, potassium oxide with a particle size of 100 mesh and a weight ratio of 18%, and barium hydroxide powder with a particle size of 90 mesh and a weight ratio of 18% to the mixing equipment in sequence, and stir the three added powders evenly;

[0071] 2) Add polyimide powder with a particle size of 180 mesh and a weight ratio of 5% to the above mixture again, and stir again to make the two mix evenly;

[0072] 3) Add two powders of PEG-4000 with a particle size of 100 mesh and a weight ratio of 7% and microcrystalline wax with a particle size of 50 mesh and a weight ratio of 4% to the above mixture again, and stir evenly again to obtain the powder curing agent of the present invention.

[0073] Compared with the sand mold produced by using the powder curing agent prepared in Example Three and using phenolic resin as the binder and the same kind of sand mold produced without mixing the powder curing agent of the present invention in the molding sand, the relevant performance has been significantly improved. Specifically, as shown in Table 3, Table 3 is a comparison table of the performance indicators of the sand mold produced or printed with the sand mold added with the powder curing agent prepared in Example Three and the same sand mold produced or printed without adding the powder curing agent.

[0074] Table 3 Comparison Table of Performance Indicators of Example Three

[0075]

[0076] As can be seen from the detection results in Table 3, after adding the powder curing agent of the present invention, the various performance indicators of the sand mold have been significantly improved, achieving the expected effect.

[0077] Example Four

[0078] The preparation method of the powder curing agent of the present invention includes

[0079] 1) Add silicon dioxide with a particle size of 100 mesh and a weight ratio of 55%, sodium silicate with a particle size of 140 mesh and a weight ratio of 15%, calcium oxide with a particle size of 120 mesh and a weight ratio of 10%, and zinc hydroxide powder with a particle size of 140 mesh and a weight ratio of 6% to the mixing equipment in sequence, and stir the four added powders evenly;

[0080] 2) Add polyhexamethylene adipamide powder with a particle size of 200 mesh and a weight ratio of 7% to the above mixture, and stir again to make the two evenly mixed;

[0081] 3) Add two kinds of powder materials, PEG-6000 with a particle size of 80 mesh and a weight ratio of 5% and polyethylene wax with a particle size of 70 mesh and a weight ratio of 2% to the above mixture, and stir evenly again to obtain the powder curing agent of the present invention.

[0082] Compared with the sand mold produced by using the powder curing agent prepared in Example 4 and using phenolic resin as a binder and the same kind of sand mold produced without mixing the powder curing agent of the present invention in the molding sand, the relevant properties have been significantly improved, as shown in Table 4 specifically. Table 4 is a comparison table of various performance indicators of the sand mold produced or printed by the molding sand added with the powder curing agent prepared in Example 4 and the same molding sand produced or printed without adding the powder curing agent.

[0083] Table 4 Comparison Table of Performance Indicators of Example 4

[0084]

[0085] It can be seen from the test results in Table 4 that after adding the powder curing agent of the present invention, various performance indicators of the sand mold have been significantly improved, achieving the expected effect.

[0086] Example 5

[0087] The preparation method of the powder curing agent of the present invention includes,

[0088] 1) Add calcium silicate powder with a particle size of 120 mesh and a weight ratio of 52%, sodium oxide powder with a particle size of 200 mesh and a weight ratio of 8%, and aluminum hydroxide powder with a particle size of 10 mesh and a weight ratio of 8% to the mixing equipment in sequence, and stir the three added powder materials evenly;

[0089] 2) Add polycaprolactam powder with a particle size of 100 mesh and a weight ratio of 10% to the above mixture, and stir again to make the two evenly mixed;

[0090] 3) Add two kinds of powder materials, PEG-2000 with a particle size of 60 mesh and a weight ratio of 16% and microcrystalline wax with a particle size of 100 mesh and a weight ratio of 6% to the above mixture, and stir evenly again to obtain the powder curing agent of the present invention.

[0091] Compared with the sand mold produced by using the powder curing agent prepared in Example 5 and using phenolic resin as the binder and the same kind of sand mold produced without mixing the powder curing agent of the present invention in the molding sand, the relevant performance has been significantly improved. Specifically, as shown in Table 5, Table 5 is a comparison table of various performance indexes of the sand mold produced or printed by the molding sand added with the powder curing agent prepared in Example 5 and the same molding sand produced or printed without adding the powder curing agent.

[0092] Table 5 Comparison Table of Performance Indexes of Example 5

[0093]

[0094] It can be seen from the test results in Table 5 that after adding the powder curing agent of the present invention, various performance indexes of the sand mold have been significantly improved, achieving the expected effect.

[0095] Using the molding sand mixed with the powder curing agent of the present invention to print the sand mold has greatly improved the efficiency and quality of producing the sand mold by spraying and printing with phenolic resin binder. Specifically, it includes the following aspects:

[0096] (1) The powder curing agent of the present invention is in a solid powder state, and all the raw materials used are in powder form. The process configuration process is simple and the production efficiency is high;

[0097] (2) Several powder raw materials in the powder curing agent of the present invention are graded with different particle size specifications. When added to the 3D printing molding sand, it can improve the close packing of the printed sand mold, reduce the porosity of the sand mold, increase the density and strength of the sand mold, and make the internal and surface denseness of the sand mold better and the dimensional accuracy higher;

[0098] (3) The powder curing agent of the present invention adds a silicon-containing compound. After adding it to the 3D printing molding sand, it can participate in the reaction during the reaction of the organic ester curing agent and the 3D room temperature curing phenolic resin and provide a three-dimensional cross-linked structure, which can increase the strength of the sand mold by 10% - 25%;

[0099] (4) Adding metal oxides to the powder curing agent of the present invention can react with the moisture in the resin to reduce the moisture content in the sand mold. In addition, the heat released by the reaction with water can increase the temperature inside the sand mold. After the reaction, it improves the alkaline environment required for the reaction of phenolic resin and organic ester curing agent. All of the above can promote the reaction of phenolic resin and organic ester curing agent and accelerate the hardening speed of the sand mold. It can accelerate the hardening speed of the sand mold by 10% - 30%, shorten the cleaning box time by 1 - 3h, and increase the strength of the sand mold by 5% - 15%;

[0100] (5) A metal hydroxide is added to the powder curing agent of the present invention. The metal hydroxide dissolves in water and releases heat, which can increase the temperature inside the sand mold, promote the reaction between phenolic resin and organic ester, and improve the hardening speed of the sand mold. Secondly, the metal hydroxide dissolves in water to be alkaline, and the stronger the alkalinity, the faster the reaction between phenolic resin and organic ester curing agent, and the faster the hardening speed of the sand mold. After adding the metal hydroxide, the hardening speed of the sand mold can be increased by 15% - 40%, the cleaning box time can be shortened by 2 - 4 hours, and the strength of the sand mold can be increased by 10% - 25%.

[0101] (6) An amide polymer is added to the powder curing agent of the present invention to modify the structure during the hardening of phenolic resin, which can improve the toughness of the phenolic resin sand mold, increase the room temperature strength and high temperature strength of the sand mold, and can increase the room temperature strength of the sand mold by 10% - 30% and the high temperature strength by 15% - 30%.

[0102] (7) An ethylene glycol polymer is added to the powder curing agent of the present invention to achieve a toughening effect, improve the toughness of the phenolic resin sand mold, reduce the brittleness of the phenolic resin sand mold, and avoid cracking or breaking of the sand mold during cleaning box, lifting and core assembling.

[0103] (8) Solid paraffin is added to the powder curing agent of the present invention, which can improve the toughness and hardness of the phenolic resin sand mold, reduce the brittleness of the phenolic resin sand mold, and avoid cracking or breaking of the sand mold during cleaning box, lifting and core assembling. In addition, in a humid environment, the hydrophobicity of paraffin helps the structure of the hardened phenolic resin not to be eroded by moisture, improves the moisture resistance of the phenolic resin sand mold, and improves the situation of sand dropping on the surface of the sand mold after being affected by moisture.

[0104] The above embodiments are only descriptions of a typical application of the technical solution of the present invention. On the basis of being reasonable and without creative labor, reasonable expansion can also be carried out.

Claims

1. A powder curing agent, characterized in that, The powder materials included are silicon-containing compounds, metal oxides, metal hydroxides, amide polymers, ethylene glycol polymers, and solid paraffin; among them, the weight percentages of each component are 28%-70% for the silicon-containing compound, 8%-27% for the metal oxide, 6%-18% for the metal hydroxide, 5%-20% for the amide polymer, 4%-16% for the ethylene glycol polymer, and 2%-12% for the solid paraffin.

2. The powder curing agent according to claim 1, characterized in that, The silicon-containing compound is one or more of silicides and silicates. Specifically, the silicide can be one or more of silicon dioxide, calcium silicide, magnesium silicide, silicon carbide, silicon nitride, and silicon chloride; the silicate can be one or more of sodium silicate, potassium silicate, magnesium silicate, aluminum silicate, calcium silicate, lithium silicate, and sodium metasilicate.

3. The powder curing agent according to claim 1, wherein The metal oxide is one or more of lithium oxide, sodium oxide, potassium oxide, magnesium oxide, calcium oxide, aluminum oxide, zinc oxide, iron oxide, barium oxide, and titanium oxide.

4. The powder curing agent according to claim 1, wherein The metal hydroxide is one or more of calcium hydroxide, magnesium hydroxide, barium hydroxide, aluminum hydroxide, zinc hydroxide, and iron hydroxide.

5. The powder curing agent according to claim 1, characterized in that, The amide polymer is one or more of polyamide, polyimide, polyacrylamide, polycaprolactam, polyhexamethylene adipamide, polyamide ester, polyimide carbazine, and heterocyclic polyamide.

6. The powder curing agent according to claim 1, characterized in that, The ethylene glycol polymer is one or more of PEG-1500, PEG-2000, PEG-3000, PEG-4000, PEG-6000, and PEG-8000.

7. The powder curing agent according to claim 1, characterized in that, The solid paraffin can be microcrystalline wax and polyethylene wax.

8. A preparation method of a powder curing agent, characterized in that, Including, S01, sequentially add the silicon-containing compound powder with a weight ratio of 28%-70%, the metal oxide powder with a weight ratio of 8%-27%, and the metal hydroxide powder with a weight ratio of 6%-18% to the mixing equipment, and stir the powders evenly. S02, add the amide polymer powder with a weight ratio of 5%-20% to S01, and stir the powders evenly again. S03, add the ethylene glycol polymer powder with a weight ratio of 4%-16% and the solid paraffin powder with a weight ratio of 2%-12% to S02, and stir the powders evenly again to obtain the powder curing agent.

9. A method for using a powder curing agent, characterized in that, Including, S11, add the powder curing agent accounting for 0.3%-3% of the weight of the molding sand to the molding sand and mix evenly. S12, add the liquid organic ester curing agent accounting for 0.1%-0.6% of the weight of the molding sand to the product obtained in S11 and mix evenly. S13, add the product obtained in S12 to the powder spreader of the sand mold additive manufacturing equipment, and use the product obtained in S12 to lay the powder layer. S14, spray phenolic resin as a binder on the powder layer laid in S13, and cycle layer by layer to realize the printing of the sand mold.

Citation Information

Patent Citations

  • A silica hydrogel modified cold-hardening phenolic resin

    CN115141329B